No deformation propagation outward of the plateau across the Yalong Thrust Belt in Southeast Tibet - Pitard, P.; Replumaz, A.; Leloup, P.H.; Chevalier, M.-L.; Wang, S.; Bai, M.; Ou, X.; Bernet, M.; Balvay, M.; Sobel, E.R.; Vezinet, A.; Gautheron, C.; et al. (Tectonophysics, 2025)
In Southeast Tibet, the Yalong Thrust Belt (YTB) is an ideal area to test a model of thrust propagation following the collision between India and Asia. We investigate the role of the Jinhe thrust, the southernmost fault of the YTB, by dating 34 samples from four profiles using various thermochronometers. We find that the Jinhe thrust was active before ∼30 Ma, when continental Tibetan lithosphere subduction occurred at the scale of the plateau along the Jinsha suture. The Jinhe thrust is located above the South China craton edge, thickening its upper crust. The Jiulong thrust and the Muli thrust, hinterland faults of the YTB located west of the craton, were also active at that time. During the Miocene, only the Jiulong and Muli thrusts have been re-activated from ∼12.5 to 5 Ma. Therefore, no migration of the deformation occurred outwards of the plateau, as migration was limited to the east by the South China craton. The thickening of the more deformable crust occurred west of the craton, squeezed between the craton and the Eastern Himalayan syntaxis. We propose a revised tectonic reconstruction at the scale of the plateau, to illustrate the evolution of Southeast Tibet in connection with the indentation of the Indian continent. •The Yalong Thrust Belt was active before ∼30 Ma•The southernmost Jinhe thrust thickened the South China craton edge upper crust•Only the hinterland faults of the belt have been re-activated during the Miocene•Thickening occurred only west of the craton during the Miocene•The South China craton limits the outward propagation of the deformation